Analyzing the Role of University Industry-Collaboration to Regional Development: The Case Study of Bursa Region in Turkey - Taskın, Cagatan; Tuncel, Cem Okan (European Journal of Social Science Education and Research, 2014)
This study examines the contributions of university-industry collaboration to regional development. Regional development that becomes possible through allocation of the regional resources to technology development efforts provides competitiveness. in addition, university-industry collaboration is a vital centre of competence to help tackle social challenges and drive regional development. When companies and universities work in tandem to push the frontiers of knowledge, they become a powerful engine for innovation and economic growth. Due to having limited R-D capability and human capital university-industry collaboration is the main source of the innovative skills trigger the regional development and provides competitive power in the developing countries. This study aims to address the challenge of bridging the industry-university in regional development process and analyzing university-industry connection problems from local firms’ perspectives in Bursa region, Turkey. University-industry collaboration is the main important driving force for Bursa economy, a bridge between Istanbul and South Marmara region and an old city that has strong industrial infrastructure in Turkey. It has a great potential to become a competitive region because of the fact that it has many innovative firms clustered under different sectors. Some technological spillovers, provided by breakthroughs in Bursa economy, will enable to the creation of an innovative region from South Marmara. To reach the success in this process, an interfaced institution which construct and coordinate university-industry collaboration have to be developed. in this study, university-industry collaboration is evaluated from the viewpoint of firms. A structured questionnaire was formed through a literature survey. The main population of this research consists of manufacturing industry in Bursa region, Turkey. The data was collected from selected manufacturing firms in order to evaluate the challenges and the expectations of these firms. Based on the obtained results, policy alternatives that aim to develop university-industry collaboration more effectively in the region were also discussed.